The Effect of the Quality of the E-Open Service System of the Population and Civil Registration Service on User Satisfaction in Bekasi City - Tata Tiara Dwi Indrianti; Hilma Mutiara Winata (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Abstract This study aims to analyze the influence of system quality and electronic service quality on the level of user satisfaction of E-Open services in Bekasi City. This study uses a quantitative approach with a descriptive method. The sampling method applied is two-stage sampling, then analyzed using SmartPLS version 3.2.9 to analyze the relationship between variables. The research findings show that system quality has a positive and significant impact on user satisfaction, indicated by a path coefficient value of 0.566 and an F-square value of 0.364. In addition, electronic service quality is also proven to have a significant effect on user satisfaction, with a path coefficient value of 0.346 and an F-square value of 0.136. Simultaneously, both system quality and electronic service quality together have a significant influence on user satisfaction, with an F-count value reaching 703.767. These results strengthen that improvements in the overall quality of systems and electronic services can encourage increased user satisfaction. Keywords: Electronic Service Quality, E-Open, System Quality, User Satisfaction